2014 Twentieth National Conference on Communications (NCC) 2014
DOI: 10.1109/ncc.2014.6811306
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of TV white space in India

Abstract: Abstract-Licensed but unutilized television (TV) band spectrum is called as TV white space in the literature. Ultra high frequency (UHF) TV band spectrum has very good wireless radio propagation characteristics. The amount of TV white space in the UHF TV band in India is of interest. Comprehensive quantitative assessment and estimates for the TV white space in the 470-590MHz band for four zones of India (all except north) are presented in this work. This is the first effort in India to estimate TV white spaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 11 publications
0
31
0
2
Order By: Relevance
“…TVWS are vacant channels (or guard bands) between used radio bands that were allocated to avoid interference between adjacent used channels. Several measurement studies carried out on spectrum occupancy have reported that most of the allocated spectrum is currently heavily underutilized [1], [2,[3], [4]. Furthermore, analyzing the recent deployments of TVWS networks in developing countries, we can draw the following conclusions:…”
Section: Introductionmentioning
confidence: 80%
“…TVWS are vacant channels (or guard bands) between used radio bands that were allocated to avoid interference between adjacent used channels. Several measurement studies carried out on spectrum occupancy have reported that most of the allocated spectrum is currently heavily underutilized [1], [2,[3], [4]. Furthermore, analyzing the recent deployments of TVWS networks in developing countries, we can draw the following conclusions:…”
Section: Introductionmentioning
confidence: 80%
“…Often there is no threshold that simultaneously gives low false positives and low false negatives. The Federal Communications Commission (FCC), the US regulator, mandates a sensing sensitivity threshold of −114 dBm by WSDs, which is considered as way too conservative by many in the literature and leads to waste of TVWS as well as increased complexity in the sensing device [4,23,27,28]. In terms of protecting primary TV services from interference, higher threshold values might be cause of interference while lower threshold values lead to inefficient spectrum utilization.…”
Section: Detection Thresholdmentioning
confidence: 99%
“…In this quest, government institutions, research institutions, and other stakeholders around the world have performed measurements and studied the occupancy of the already allocated part of the radio frequency spectrum. The measurements have revealed that most of the allocated radio frequency spectrum is heavily underutilized except for the radio frequency spectrum allocated to cellular technologies, and the Industrial, Scientific and Medical (ISM) bands [4]. The underutilization is more apparent in the TV broadcasting frequency band where it has shown to be unused [5][6][7][8] most of the time.…”
Section: Introductionmentioning
confidence: 99%
“…ISO/IEC 16504 is a adapted version of ECMA-392 standard for the same application with comparable system structure. IEEE 802 standard group has some working group (WG) for TV white space [6]. IEEE 802.22 WG has issued a standard for wireless regional area networks (WRAN) [7].…”
Section: Introductionmentioning
confidence: 99%